2010
DOI: 10.1183/09031936.00197309
|View full text |Cite
|
Sign up to set email alerts
|

Exercise reduces airway sodium ion reabsorption in cystic fibrosis but not in exercise asthma

Abstract: When ventilating large volumes of air during exercise, airway fluid secretion is essential for airway function. Since these are impaired in cystic fibrosis and exercise-induced asthma, it was the aim of this study to determine how exercise affects airway Na + and Cl -transport and whether changes depend on exercise intensity. Nasal potential was measured in Ringer's solution, with amiloride to block Na + transport, and in low chloride-containing isoproterenol to assess Cl -channels. Nasal potential was measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 31 publications
2
16
0
Order By: Relevance
“…However, we found a significant reduction in sputum solids content in the five minutes following treadmill exercise but not after Flutter® therapy. Previously researchers have shown an inhibition of sodium conductance channels [11, 12, 37] and altered ion regulation with submaximal cycle exercise in adults with CF [13], suggesting improved airway hydration or airway surface liquid, however these changes only lasted for four minutes after ceasing exercise [37]. Our study provides some evidence to support the proposed increase in mucus water content with exercise in CF [1012].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…However, we found a significant reduction in sputum solids content in the five minutes following treadmill exercise but not after Flutter® therapy. Previously researchers have shown an inhibition of sodium conductance channels [11, 12, 37] and altered ion regulation with submaximal cycle exercise in adults with CF [13], suggesting improved airway hydration or airway surface liquid, however these changes only lasted for four minutes after ceasing exercise [37]. Our study provides some evidence to support the proposed increase in mucus water content with exercise in CF [1012].…”
Section: Discussionsupporting
confidence: 80%
“…Previously researchers have shown an inhibition of sodium conductance channels [11, 12, 37] and altered ion regulation with submaximal cycle exercise in adults with CF [13], suggesting improved airway hydration or airway surface liquid, however these changes only lasted for four minutes after ceasing exercise [37]. Our study provides some evidence to support the proposed increase in mucus water content with exercise in CF [1012]. The 1.2% reduction in sputum solids content that we observed is likely to be clinically significant as it is similar to that achieved with mannitol in people with CF, [28] which results in significant improvements in mucus clearance [38] and lung function in the long term [39].…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has demonstrated that exercise inhibits ENaC as observed by a reduction in the ΔAmil response from baseline with exercise 12,43 . Our study did not demonstrate this same finding, but instead found ΔAmil was larger with exercise for both CF and healthy subjects.…”
Section: Discussionmentioning
confidence: 96%
“…More recently, the benefits of exercise have been extended to a more cellular level with demonstration of inhibition of ENaC activity with exercise, thereby potentially improving ion regulation. With the goals of treatment therapy in CF to 1) prevent or minimize decline in lung function and 2) ameliorate impairments in ion regulation, exercise has convincingly demonstrated its ability to facilitate the former and research is now suggesting it may also aid in the latter 1113 .…”
Section: Introductionmentioning
confidence: 99%
“…It is conceivable that airway lining fluid Na + content could augment osmolarity in the airways during exercise. In this regard, Schmitt et al (77) established that, in airway epithelia from asthmatic patients with EIB, transepithelial nasal potential carried out by Cl − and Na + is not modified during exercise, indicating that a Na + handling mechanism is at stake. Also associated with impaired cellular Na + homeostasis, is the inhibition of the NKA in atopy and EIB.…”
Section: The Paradox Of Exercise-induced Bronchoconstrictionmentioning
confidence: 99%